2015
DOI: 10.1038/onc.2015.160
|View full text |Cite
|
Sign up to set email alerts
|

Plexin-B1 signalling promotes androgen receptor translocation to the nucleus

Abstract: Semaphorins and their receptors plexins have diverse roles in many cancers affecting tumour growth, metastasis and angiogenesis. Plexin-B1, the receptor for semaphorin4D (Sema4D), has been implicated in prostate cancer where mutation of the gene and overexpression of the protein occur. It is not clear, however, as to which of the several Sema4D-activated signalling pathways downstream of plexin-B1 function in prostate cancer progression. We show here that Sema4D/plexin-B1 increases the expression of androgen-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…In vitro assays also demonstrated NSCLC cell lines H1299, HCC827, A549 and H1975 had a high level of sema4D expression, however, they have various ability to form vascular‐like channels in matrigel. As previous studies reported, sema4D plays important roles in diverse physiological processes such as tumor cell proliferation, survival, migration, invasion, tumor angiogenesis and immunity, and this may be the reason why NSCLC tissues and cell lines had a high level of sema4D. On the other hand, VM channels were all detected in Sema4D‐positive NSCLC tissues and in none of Sema4D‐negative samples in our study (Fig.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In vitro assays also demonstrated NSCLC cell lines H1299, HCC827, A549 and H1975 had a high level of sema4D expression, however, they have various ability to form vascular‐like channels in matrigel. As previous studies reported, sema4D plays important roles in diverse physiological processes such as tumor cell proliferation, survival, migration, invasion, tumor angiogenesis and immunity, and this may be the reason why NSCLC tissues and cell lines had a high level of sema4D. On the other hand, VM channels were all detected in Sema4D‐positive NSCLC tissues and in none of Sema4D‐negative samples in our study (Fig.…”
Section: Discussionsupporting
confidence: 66%
“…The high‐affinity Sema4D receptor plexinB1 is mainly expressed in endothelial and epithelial cells . The role of Sema4D/plexinB1 signaling in regulating tumor angiogenesis has been widely studied . Our studies revealed that the regulatory effect of Sema4D on VM formation in NSCLC cells also relied on binding with plexinB1 (Figs.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However we have detected the presence of a neural-derived regulatory protein, Sema3C (data not shown), that may indicate the inclusion of a neural tissue extract. Given reports that PCa cells express a Semaphorin receptor (Plexin B1) and are influenced by Semaphorins [35, 36], perhaps Semaphorin signaling plays some role in the model we described.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, Yu et al 's results also identify ARBSs in nearly all other class 3 semaphorins, most notably three ARBSs in another class 3 semaphorin with well-documented tumor-promoting activity, SEMA3E. Conversely, receptors to semaphorins have been shown to promote AR activity [84]. …”
Section: Discussionmentioning
confidence: 99%